Knowledge, Attitude and Practice of Hospital Acquired Infection Prevention Among Medical Students at Alkhoms Faculty of Medicine Elmergib University 2025 - Mohamed Sryh; Walid Lamiri (African Journal of Advanced Pure and Applied Sciences, 2026)
Background: Medical students’ knowledge, attitude and practice (KAP) regarding hospital acquired infections (HAIs) pose a significant risk to patient safety, as HAIs are a significant cause of morbidity and mortality worldwide. This study aims to evaluate KAP of medical students at Alkhoms faculty of medicine regarding HAIs prevention and control. Methods: descriptive cross sectional design study using a Self-administered online questionnaire sent to all students at Alkhoms faculty of medicine Elmergib University at Alkhoms city Libya in April and May 2025. Results: among all 374 targeted students only 127 responded with 34% response rate. 80.3% of participants aged less than 28 years and 74% of them were females. The level of knowledge was good among 85% of participants, but there were some gaps in their attitude regarding the availability of HAIs prevention facilities and regarding hand hygiene performance. Conclusion: low response rate highlights the weak compliance of faculty students regarding medical research and performance evaluation. Our participants kknowledge regarding HAIs was good, but that was not the case with their attitude and compliance. more training programs and knowledge sessions regarding HAIs prevention should be performed, more resources should be allocated by hospital administrators regarding hand hygiene materials and facilities availability.